Association among H. pylori virulence markers dupA, cagA and vacA in Brazilian patients - Pereira,Weendelly Nayara (2014)
Background:Only a few Helicobacter pylori-infected individuals develop severe gastric diseases and virulence factors of H. pyloriappear to be involved in such clinical outcomes. Duodenal ulcer promoting gene A (dupA) is a novel virulence factor ofHelicobacter pylori that is associated with duodenal ulcer development and reduced risk for gastric carcinoma in some populations. The aims of the present study were to determine the presence ofdupA gene and evaluate the association amongdupA and other virulence factors includingcagA and vacA in Brazilian patients. Gastric biopsies were obtained from 205 dyspeptic patients (100 children and 105 adults). DNA was extracted and analyzed for the presence of H. pylori and its virulence factors using the polymerase chain reaction method.Results:Patients with gastritis tested positive for H. pylori more frequently. The dupA gene was detected in 41.5% of them (85/205); cagA gene was found in 98 isolates (47.8%) andvacA genotype s1/m1 in 50.2%, s1/m2 in 8.3%, s2/m2 in 36.6%, s2/m1 in 0.5% and s1/s2/m1/m2 in 4.4%. We also verified a significant association between cagA and dupA genes [p = 0.0003, relative risk (RR) 1.73 and confidence interval [CI] = 1.3-2.3]. The genotypes s1/m1 were also associated with dupA gene (p = 0.0001, RR: 1.72 and CI: 1.3-2.2). The same associations were found when analyzing pediatric and adult groups of patients individually.Conclusion:Ours results suggest that dupA is highly frequent in Brazilian patients and is associated with cagA gene andvacA s1/m1 genotype, and it may be considered an important virulence factor in the development of gastric diseases in adults or children.